Blood alcohol levels in suicide cases. Issue 3 (June 1992) - Hayward, L; Zubrick, S R; Silburn, S
Abstract : STUDY OBJECTIVE–The aim was to investigate the relationship between alcohol consumption prior to suicide and the act of suicide. DESIGN–This was a retrospective total ascertainment survey of a three year cohort of suicides in Western Australia. SETTING–Coroner's records of suicide in Western Australia between 1986 and 1988 inclusive. PARTICIPANTS–The study involved 515 consecutive suicides: 414 males and 101 females. MAIN RESULTS–Information on blood alcohol levels at time of death, presence of other drugs at time of death, drug and alcohol abuse history, psychiatric history, life events prior to death and method of suicide were collected. It was found that 35.8% of cases had a positive blood alcohol reading. Those who had been drinking alcohol prior to suicide were younger, more likely to be male, more likely to have chosen carbon monoxide as the method of suicide, more likely to have experienced a break up of a relationship and less likely to have sought professional help than those who had not been drinking. CONCLUSIONS–Data from the present study do not provide evidence for a causal relationship between alcohol consumption and suicide. Differences between those who had consumed alcohol and those who had not are suggestive of a contributory role of alcohol to a decision to commit suicide in a subset of suicide cases.